Critical Discourse Analysis of America’s Former president Barack Obama’s Speech on the Death of Osama Bin Laden - Tahir, Samia; Riaz, Neelma; Sukhera, Faisal Arif (Pakistan Languages and Humanities Review, 2025)
This paper aims to make the speech more relevant to current global realities, considering how political rhetoric has evolved in a more digitally connected and critical world. Critical Discourse Analysis (CDA), applicable to both spoken and written texts, enables scholars to delve into the deeper meanings of social roles and the embedded power structures within a discourse. The current study revisits the speech of former U.S. President Barack Obama announcing the death of Al-Qaeda leader Osama Bin Laden, using Fairclough’s (1995) framework. While the speech was originally delivered in 2011, its rhetorical significance and underlying ideological assumptions continue to resonate in the post-pandemic geopolitical context. Newer studies on political discourse (Van Dijk, 2022; Hart, 2023) emphasize the long-lasting effects of such speeches on public memory, global power dynamics, and media representations. Findings endorse the role of discourse in reaffirming America’s hegemonic status through language strategies that reflect dominance and authority.